2018
DOI: 10.9740/mhc.2018.05.127
|View full text |Cite
|
Sign up to set email alerts
|

Role of antidepressants in the treatment of adults with anorexia nervosa

Abstract: Introduction:Anorexia nervosa (AN) is a severe psychiatric disorder that is difficult to treat and is associated with frequent relapses and high mortality rates. Psychiatric symptomatology (eg, depression, anxiety, obsessive-compulsive disorder/behaviors) are common comorbidities. This review provides current information about safety and efficacy of antidepressant therapy for management of AN in adults.Methods:A literature review of randomized controlled trials, open-label studies, and case reports with adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 43 publications
0
23
0
7
Order By: Relevance
“…In subsequent years, other literature reviews have been published, focused either on a specific pharmacological class (e.g. ‘antidepressants’, ‘antipsychotics’) (Dold et al, 2015; Marvanova and Gramith, 2018), or did not rigorously select RCTs, including studies with less rigorous methods (Marvanova and Gramith, 2018; Miniati et al, 2016). In the last decade, psychopharmacology has been enriched with the release of new molecules (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent years, other literature reviews have been published, focused either on a specific pharmacological class (e.g. ‘antidepressants’, ‘antipsychotics’) (Dold et al, 2015; Marvanova and Gramith, 2018), or did not rigorously select RCTs, including studies with less rigorous methods (Marvanova and Gramith, 2018; Miniati et al, 2016). In the last decade, psychopharmacology has been enriched with the release of new molecules (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses could further explain the fact that pharmacotherapy does not have any significant effect on AN. Some authors suggested that the state of malnutrition present in patients suffering from AN could compromise the functioning of antidepressant drugs, because of alterations in serotonin metabolism caused by diminished circulating tryptophan and gonadal steroids (Ferguson et al, 1999), and of structural and functional brain changes (Marvanova and Gramith, 2018). Additionally, the results of the studies carried out with neuroimaging techniques on patients with AN suggest the presence of alterations at the level of the dopaminergic system, such as an altered sensitivity to the D2 receptor, a decrease in intrasynaptic dopamine, or an altered density of D2/D3 receptors (Phillipou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Significant relationships between poorer self-reported oral health outcomes, lower socioeconomic status and mental health vulnerabilities were also noted [ 22 24 ]. Specifically for individuals with a mental health condition, barriers to maintaining oral health included a reduced awareness of the presence/risk of oral health problems, the affect of medications such as antidepressants resulting in manifestations such as dry mouth, lower self-esteem and body image, poor diet and fear and distrust of dental providers [ 24 26 ]. Although individuals with ED were generally found to be concerned about their teeth especially the long term impact of dental issues such as enamel erosion [ 27 , 28 ], their perceived barriers for not seeking dental intervention included reduced energy levels, anxiety, uncertainty about oral hygiene and distrust of dental providers [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the first SSRI on the market, fluoxetine (FLX), originally marketed as Prozac [24], continues to be prescribed as generic pharmacological treatment for major depression, as well as additional conditions such as obsessive-compulsive disorder [25], anxiety [26], pre-menstrual dysphoric disorder [27], and eating disorders [28]. FLX remains the most studied SSRI with regard to both human health [29] and aquatic toxicology [30].…”
Section: Introductionmentioning
confidence: 99%